Influence of deep learning-based journal reading guidance system on students’ national cognition and cultural acceptance - Huang, Wei; Song, Fangbin; Zhang, Shenyu; Xia, Tian (Frontiers in Psychology, 2022)
The purpose is to explore new cultivation modes of college students' national cognition & cultural acceptance. Deep Learning (DL) technology and Educational Psychology theory are introduced, and the influence of art journal reading on college students' national cognition & cultural acceptance is analyzed under Educational Psychology. Firstly, the background of Educational Psychology, national cognition & cultural acceptance, and learning system are discussed following a literature review. The DL technology is introduced to construct the journal reading guidance system. The system can provide users with art journals and record the user habits like reading duration and preferences. Secondly, hypotheses are proposed, and a questionnaire survey is designed, with 12 specific indicators to investigate and collect research data. Finally, the collected data are analyzed. The results show that women's cognition of Chinese traditional culture, Chinese excellent revolutionary culture, and Chinese national identity is higher than that of men. By comparison, men's cognition of Chinese advanced socialist culture is higher than women's. After using the journal reading guidance system, the cognition of female college students on traditional Chinese culture is improved by 16.3%. Before and after reading art journals, the overall national cognition & cultural acceptance of Minority students are higher than that of Han students. The overall cognition of Literature and History students is higher than that of Science and Engineering students in traditional Chinese culture and China's excellent revolutionary culture and lower in advanced Chinese socialist culture and Chinese national identity. The overall cognition of college students' party members to the advanced socialist culture is higher than league members. As students read more art journals through the guidance system, their overall national cognition & cultural acceptance have increased. Therefore, reading art journals can promote college students' national cognition & cultural acceptance. A national cognition & cultural acceptance promotion system that conforms to the current situation of college students is constructed. The finding provides a reference for developing complex emotion recognition technology in human-computer interaction.